Magnesium and Hemorrhage Volume in Patients With Aneurysmal Subarachnoid Hemorrhage. Issue 1 (January 2020) - Liotta, Eric M.; Karmarkar, Ameeta; Batra, Ayush; Kim, Minjee; Prabhakaran, Shyam; Naidech, Andrew M.; Maas, Matthew B.
Abstract : Objectives: We tested the hypothesis that admission serum magnesium levels are associated with extent of hemorrhage in patients with aneurysmal subarachnoid hemorrhage. Design: Single-center prospective observational study. Setting: Tertiary hospital neurologic ICU. Patients: Patients with aneurysmal subarachnoid hemorrhage. Interventions: Clinically indicated CT scans and serum laboratory studies. Measurements and Main Results: Demographic, clinical, laboratory, and radiographic data were analyzed. Extent of initial hemorrhage was graded semi-quantitatively on admission CT scans using the modified Fisher scale (grades: 0, no radiographic hemorrhage; 1, thin [< 1 mm in depth] subarachnoid hemorrhage; 2, thin subarachnoid hemorrhage with intraventricular hemorrhage; 3, thick [≥ 1 mm] subarachnoid hemorrhage; 4, thick subarachnoid hemorrhage with intraventricular hemorrhage). We used both ordinal (modified Fisher scale) and dichotomized (thick vs thin subarachnoid hemorrhage) univariate and adjusted logistic regression models to assess associations between serum magnesium and radiographic subarachnoid hemorrhage severity. Data from 354 patients (mean age 55 ± 14 yr, 28.5% male, median admission Glasgow Coma Scale 14 [10–15]) were analyzed. Mean magnesium was lower in patients with thick versus thin subarachnoid hemorrhage (1.92 vs 1.99 mg/dL; p = 0.022). A monotonic trend across categories of modified Fisher scale was found using analysis of variance and Spearman rank correlation ( p = 0.015 and p = 0.008, respectively). In adjusted ordinal and binary regression models, lower magnesium levels were associated with higher modified Fisher scale (odds ratio 0.33 per 1 mg/dL increase; 95% CI, 0.14–0.77; p = 0.011) and with thick subarachnoid hemorrhage (odds ratio 0.29 per 1 mg/dL increase; 95% CI, 0.10–0.78; p = 0.015). Conclusions: These data support the hypothesis that magnesium influences hemorrhage severity in patients with aneurysmal subarachnoid hemorrhage, potentially through a hemostatic mechanism.